Desigualdade racial nos espaços escolares e o trabalho do assistente social - Freitas, Tais Pereira De; Engler, Helen Barbosa Raiz (Cortez Editora Ltda, 2015)
The text presented here focuses on the reflection on the repercussions of racial inequality in the spaces of the educational system that are configured crucial both for reproduction and for coping with the uneven condition. Thus it is considered the potential for the school construction process of racial equality and ethical commitment of social work in building a other social order, seeking to argue the role of the social worker integration in public education policy.

O texto ora apresentado enfoca a reflexão acerca dos rebatimentos da desigualdade racial nos espaços do sistema educacional, que se configuram fundamentais, tanto para a reprodução, quanto para o enfrentamento da condição desigual. Dessa forma, considera-se o potencial da escola para o processo de construção da igualdade racial e o compromisso ético do Serviço Social na construção de outra ordem societária, buscando-se discutir as contribuições da inserção do assistente social na política pública de educação.
Racial inequality in school and the work of social worker
Keywords: Racial inequality; Public education policy; Social Work; Desigualdade racial; Política pública de educação; Serviço Social